Percepción Social de los Riesgos Antrópicos Ante el Cierre Técnico del Botadero de Basura, en el Sector Curgua, Parroquia Santa Fe del Cantón Guaranda, Periodo Mayo – Septiembre 2023 - Guerrero Ramírez, Carol Nathaly (2023)
Research on solid waste management in Curgua is of fundamental importance in addressing anthropogenic risks and their impact on the health of the community. This study is a response to a global problem of growing concern for public health and environmental sustainability. The relevance of this research lies in its ability to identify, understand and propose concrete solutions to the problems associated with inadequate waste disposal, not only in Curgua, but also as a valuable contribution to face similar challenges at a global level. Furthermore, this research provides a basis for the adoption of effective public policies and the implementation of practical actions to address anthropogenic risks, thus strengthening the health and well-being of the community. Despite the implementation of technical closure measures, uncertainty persists about their effectiveness. The problem is formulated as the social perception of anthropogenic health risks due to the technical closure of the landfill in the period from May to September 2023. The general objective is to determine this perception in the community, identifying the current conditions of the landfill and proposing measures to reduce the impact on the health of the inhabitants. This study seeks to provide a comprehensive view of the perception of anthropogenic risks in the inhabitants and contribute to the identification of possible improvements in pollution control measures, promoting citizen participation in solid waste management and improving the quality of life of the population. The expected achievements include a deeper understanding of the social perception of anthropogenic health risks and the formulation of concrete measures to mitigate these negative impacts in the Curgua community. In addition, this study focuses on the environmental and social effects of the technical closure of the landfill, including an assessment of air quality, soil stability, surface and groundwater, as well as the effects on flora, fauna and landscape. The perception of the inhabitants is influenced 16 by factors such as bad odors, the presence of insects and rodents, and the appearance of pollution-related diseases, which has led to a perception of insecurity in health and quality of life. This study is presented as an important starting point for understanding and addressing the anthropogenic risks to the health of the inhabitants of Curgua in the context of the technical closure of the landfill. With the information gathered, it is hoped that more informed decisions can be made and specific measures can be implemented to reduce negative health and environmental impacts, while encouraging active community participation in solid waste management. This holistic approach will contribute to the well-being and safety of the inhabitants and will serve as an example to address similar problems in other areas affected by garbage dumps in Ecuador.